Hydrodynamics and SPM transport in an engineered tidal estuary: The Adour river (France). (31st December 2019) - Defontaine, Sophie; Sous, Damien; Morichon, Denis; Verney, Romaric; Monperrus, Mathilde
Abstract: The present paper reports on a series of field experiments aiming to characterise the functioning of a man-engineered strongly forced salt-wedge estuary: the lower estuary of the Adour river, France. Bottom-moored velocity measurements and surface boat surveys have been performed under low river discharge conditions, for both neap and spring tides, in order to provide a well-documented reference framework to understand the dynamics of water masses, turbulence and suspended particulate matter (SPM) transport in the lower estuary. An additional campaign has been carried out in high river discharge conditions. This first documented in-situ study of the Adour lower estuary demonstrates its variability in terms of hydrological regimes, from salt-wedge to partially mixed regimes depending on tidal and discharge conditions. Turbulent properties showed a significant response to the variations of salinity structure, with higher values when stratification is minimal. At spring tide, a tidal variation between mixing conditions on the ebb and the flood is revealed by ADCP measurements, with higher values extended up to the surface during the ebb. The link between turbulent mixing and suspended sediment concentration is straightforward during the ebb. During the flood, the suspended sediment concentration (SSC) seems related to the salt-wedge entrance re-suspension and stratification-induced turbulence damping. No stable Estuarine Turbidity Maximum (ETM) has been observed during the field experiment in the lower Adour estuary. Abstract : The first extensive study of the lower Adour estuary. The observations reveal a very high variability of the salinity structure, which has never been reported in the literature. No ETM has been identified in the present experimental conditions. The Adour estuary dynamics is discussed with respect to the roles of tide, river discharge and human engineering.